EKOKRITIK GREG GARRARD DALAM NOVEL API AWAN ASAP KARYA KORRIE LAYUN RAMPAN DAN RELEVANSI PEMBELAJARAN SASTRA DI SEKOLAH MENENGAH ATAS - Wiradita Sawijiningrum (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2018)
This study aims to describe: (1) the relationship between the characters with the natural environment in the novel Api Awan Asap by Korrie Layun Rampan, (2) the form of damage to the natural environment in the novel Api Awan Asap by Korrie Layun Rampan, and (3) the relevance of research results to literary learning in high school. The method used in this research is descriptive qualitative method with Greg Garrard's ecocritical approach. Research data sources are the results of interviews and the novel Api Awan Asap by Korrie Layun Rampan. Data collection techniques use library techniques, see and note. Researchers play a direct role as the main instrument of research. Data validation is obtained through triangulation of data sources, methods, and theories. Data analysis used by the research is an interactive analysis analysis model by collecting data, reducing data, presenting data, and verifying data. The results of the study obtained a number of 26 citations which described in accordance with the two formulations of the problem in the study. 14 data that describes the form of relationship between characters and the natural environment and 12 data illustrate the form of natural environmental havoc. The results of this study have a suitability if relevant to literary learning in high school. Keywords: Ecocriticism, Fire of Smoke, Learning Relevance